2021
DOI: 10.1021/acs.iecr.1c01633
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methanol to Olefins over Modified OSDA-Free CHA Zeolite Catalyst

Abstract: Methanol to olefins (MTO) is an essential process that produces olefins from both renewable and fossil fuels resources. Chabazite (CHA) is an efficient catalyst for MTO process due to its distinct properties that promote light olefins (i.e., ethylene and propylene) production. Herein, we report a series of chabazite-based catalysts (OSDA-free with enhanced textural properties) that facilitate the MTO reaction. The synthesized CHA was modified by steam injection (CHA-S), acid treatment (CHA-A), steam and acid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…SAPO‐34 materials have received considerable scientific attention because of their high activity toward light olefins [55,74] . SAPO‐34 has been applied in catalytic processes, such as MTO [75–85] . Related research works [86,87] have shown that synthesizing a hierarchical structure that reduces the crystal size of the material regulates the crystal acidity, which can improve the catalytic activity of SAPO‐34, especially for MTO reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAPO‐34 materials have received considerable scientific attention because of their high activity toward light olefins [55,74] . SAPO‐34 has been applied in catalytic processes, such as MTO [75–85] . Related research works [86,87] have shown that synthesizing a hierarchical structure that reduces the crystal size of the material regulates the crystal acidity, which can improve the catalytic activity of SAPO‐34, especially for MTO reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[55,74] SAPO-34 has been applied in catalytic processes, such as MTO. [75][76][77][78][79][80][81][82][83][84][85] Related research works [86,87] have shown that synthesizing a hierarchical structure that reduces the crystal size of the material regulates the crystal acidity, which can improve the catalytic activity of SAPO-34, especially for MTO reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to distinct pore size and volume, SAPO-34 material exhibits moderate to high hydrophobicity and has high thermal and hydrothermal stability. Due to these characteristic features, SAPO-34 has been extensively used in the methanol to olefin (MTO) process [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. In recent years, SAPO-34 has been investigated for CO 2 remediation, including CO 2 capture [ 49 , 50 , 51 ], conversion [ 52 , 53 , 54 ], and separation [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been observed that the increase in the temperature attributes to more gas yield with higher hydrogen contents with the suppression of tar and char concentrations. The obtained syngas could be used to produce several fuels and chemicals. , …”
Section: Introductionmentioning
confidence: 99%
“…The obtained syngas could be used to produce several fuels and chemicals. 33,34 Air and steam are the two most commonly used gasification agents, and several studies have been conducted on the gasification of scrap tires utilizing these gasification agents to analyze their impact on the final product and the overall process. Xiao et al 35 studied the impact of equivalence ratio (ER) on the gas yield using air as a gasification agent.…”
Section: Introductionmentioning
confidence: 99%